Self-concept among Indonesian adolescents in coastal areas: A cross-sectional study - Rika Sarfika; I Made Moh. Yanuar Saifudin; Eka Oktavianto (Belitung Nursing Journal, 2023)
Background: Adolescence is a transitional phase from childhood to adulthood, characterized by various biological, psychological, and social changes. Adolescents living in coastal regions are exposed to social-environmental risk factors that can affect their emotional wellbeing, primarily due to the demanding and unpredictable nature of coastal communities. These challenging and volatile circumstances can have a negative impact on adolescents’ emotions, making them more vulnerable to mental and emotional disorders. Objective: This study aimed to examine the self-concept and its differences according to sociodemographic factors among adolescents residing in coastal areas of Indonesia. Methods: A cross-sectional design was employed for this study, which involved 644 adolescents living in coastal regions of Indonesia, specifically in the West Sumatra and Bali provinces. The Tennessee Self Concept Scale (TSCS) 2nd Edition Short Form was used to assess self-concept from August to September 2022. Descriptive statistics, Independent-t-test, and One-way ANOVA were utilized for data analysis. Results: The findings revealed that adolescents in coastal areas had a high level of self-concept. A statistically significant difference was discovered in the overall self-concept according to gender (p = 0.002). Similarly, a significant difference was observed in the physical domain based on class level (p = 0.019). Regarding the personal domain, significant differences were identified according to age (p = 0.030), class level (p = 0.030), parent's marital status (p = 0.030), father's education (p = 0.05), and family income (p = 0.01). Furthermore, in the family domain, significant differences were found based on parents’ marital status (p <0.001) and adolescents’ residence status (p = 0.002). Additionally, a significant difference in the academic domain was observed with respect to gender (p = 0.001). However, no significant differences were noted in the moral ethics and social domains across all sociodemographic variables (p >0.05). Conclusion: This study emphasizes the need for attention from various stakeholders, including mental health nurses, to prioritize interventions to promote positive self-concept among adolescents, consider sociodemographic factors that influence self-concept, and address areas of dissatisfaction such as moral behavior and academic/work efficiency. Incorporating family support and nurturing positive parent-child relationships are also important for fostering a healthy self-concept in adolescents.